Second Five Year Plan (1956-57 to 1960-61) Nanded District Bombay State - Planning Commission (Planning Commission, 1958)
Nanded is one of the five Marathwada districts now forming part of the new Bombay State. It is situated on the Bombay and Andhra Pradesh border. There is Andhra Pradesh on the South and the East, the Ycotmal district on the North, the Parbhani district on the West and the Osmanabad district on the South-West. This district has been reconstituted after reorganisation of the State and now consists of 1676 villages with a population of 9,58,888 and a total land area of 30,90.778 acres i. e. say 4700 sq. miles. The following table gives details regarding the Talukas, Mahals and Tahsils in the district.
Bombay State